L’anthropologie pour étudier le tourisme - Naomi Leite; Nelson Graburn (Mondes du Tourisme, 2010)
Focusing on anglophone anthropology, this article traces the emergence of tourism studies both as an academic field and as a cultural phenomenon. The text presents authors and key concepts that have structured the critical research of tourism since the 1970s: tourism development and its ‘impacts’; gender, sexuality and the body; tourist arts; ‘authenticity’; ‘ethnicity, identity and heritage’. The authors, then, outline different current study topics and their specific anthropological approaches: place and imagery; people and their experiences; movement, things and the global. Noting the global dimension of tourism practices and the maturity of anthropological research on tourism, the authors propose to go further by considering tourism from a holistic point of view, as an inextricable aspect of social, cultural and economic life being formed at the global scale. They trace new perspectives on links between tourism and medicine, tourism and media, tourism and power, tourism and activism, and, tourism and kinship.